Scientific Families and the Shaping of an Expertise in Analytical Chemistry in Modern Spain. - Suay-Matallana Ignacio (HoST, 2017)
This paper focuses on how two Spanish chemists—Antonio Casares Rodríguez (1812–1888), and his son José Casares Gil (1866–1961)—constructed their expertise in chemical analysis in modern Spain. It considers both their family connections and local networks as crucial elements in the consolidation of their scientific authority, as well as the importance of travels and textbook writing, in shaping expertise in places usually considered peripheral. Finally, this article shows how both experts were able to circulate between different spaces, notably the laboratory and the field, in this case natural springs and spas; the university and governmental committees and institutions, in this way forging new possibilities for the consolidation of analytical chemistry as a scientific discipline in Spain.